2017
DOI: 10.1136/jclinpath-2017-204334
|View full text |Cite
|
Sign up to set email alerts
|

Liver allograft biopsies with histological cholestasis: a clinicopathological study of 254 cases from a single centre

Abstract: AimsLiver allograft biopsy is important in the management of liver transplant (LT) recipients. Cholestasis is an indicator of liver dysfunction, and histological evidence of cholestasis can be observed in a wide range of pathological entities in the post-LT setting. In this study, we describe the clinicopathological features and significance of liver allograft biopsies with histological cholestasis over 11 years in our centre. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…Several previous studies have shown that rapamycin inhibits the basal rate of bile flow and the recovery of bile flow following IR (Bramow et al, 2001;Deters et al, 2002;Deters et al, 2001;Fehrenbach et al, 2003;Oswald et al, 2010;Picard et al, 2011). The latter is associated with impaired recovery of the liver following a liver transplant (Lo et al, 2018;Shiffman et al, 1991). Treatment of the liver with rapamycin and its analogues can also lead to drug-induced cholestasis under a variety of conditions (Bramow et al, 2001;Dandel et al, 2010;Pantano et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Several previous studies have shown that rapamycin inhibits the basal rate of bile flow and the recovery of bile flow following IR (Bramow et al, 2001;Deters et al, 2002;Deters et al, 2001;Fehrenbach et al, 2003;Oswald et al, 2010;Picard et al, 2011). The latter is associated with impaired recovery of the liver following a liver transplant (Lo et al, 2018;Shiffman et al, 1991). Treatment of the liver with rapamycin and its analogues can also lead to drug-induced cholestasis under a variety of conditions (Bramow et al, 2001;Dandel et al, 2010;Pantano et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Обструкция внепеченочных желчных протоков является частым проявлением таких заболеваний как: опухоли холедоха, холедохолитиаз, рак головки поджелудочной железы, хронический панкреатит, лимфопролиферативные заболевания, метастазы области ворот печени и головки поджелудочной железы. Обструктивный холестаз может приводить к развитию вторичного билиарного цирроза, печеночной недостаточности, острому либо хроническому рецидивирующему холангиту [1,2]. Гистологические проявления выраженности холестаза в печени имеют клиническое и прогностическое значение [2].…”
Section: Introductionunclassified
“…Обструктивный холестаз может приводить к развитию вторичного билиарного цирроза, печеночной недостаточности, острому либо хроническому рецидивирующему холангиту [1,2]. Гистологические проявления выраженности холестаза в печени имеют клиническое и прогностическое значение [2]. Обструкция внепеченочных желчных путей ведет к пролиферации эпителия желчных протоков и перипортальному фиброзу, что в эксперименте на крысах сопровождается увеличением массы и объема печени [3].…”
Section: Introductionunclassified